Drought on the Fly: UAS Mapping of Conifer Drought Stress - Lauren E. Lad; Wade T. Tinkham; Camille S. Stevens-Rumann; Melanie Vanderhoof; Jody Vogeler; Alistair M. S. Smith (Forest Science, 2026)
Foliar moisture content (FMC) plays a crucial role in arid, frequent-fire forests by influencing fire behavior, tree survival, and serving as a proxy for tree health. Management actions such as mechanical thinning, flammable fuels reduction, and prescribed fires can act to mitigate wildfire risk and improve forest health by reducing fuel connectivity, diversifying forest structure, and creating canopy gaps. These management actions could be improved by the targeted removal of moisture stressed and potentially more flammable trees during treatments. However, maps of FMC are not widely available at the tree-level, with no existing products to map FMC of western conifers at the stand-level (< 0.25 m). This project focuses on the scalability of laboratory-developed models predicting sapling FMC to develop and assess tree-level FMC in natural forest conditions. Specifically, we tested whether existing FMC models accurately predict individual tree FMC using uncrewed aerial system (UAS) data. While laboratory-developed models did not translate well to field sites, a field-developed model achieved a mean absolute error of 6.5% FMC and 81% of predictions were within 10% FMC of the observed value. In ranking the observed and predicted FMC values, the field model successfully classified trees into FMC categories with up to 85.9% accuracy. This successful classification demonstrates the utility of UAS-based FMC mapping to inform management prescriptions. Integrating UAS-derived FMC monitoring into forest management could enhance forest resilience and adaptive capacity.

Bird communities follow alternate recovery trajectories two decades after wildfire - Maria Vicini; Camille S. Stevens-Rumann; Jody C. Vogeler; Paula J. Fornwalt (Forest Ecology and Management, 2025)

Forest restoration treatments increase native plant diversity but open the door to invasion in the Colorado Front Range - Adam L. Mahood; Camille S. Stevens-Rumann; Allison E. Rhea; Scott M. Ritter; Kevin Barrett; Paula J. Fornwalt; David M. Barnard (Forest Ecology and Management, 2025)

Extreme Fire Spread Events Burn More Severely and Homogenize Postfire Landscapes in the Southwestern United States - Jessika R. McFarland; Jonathan D. Coop; Jared A. Balik; Kyle C. Rodman; Sean A. Parks; Camille S. Stevens‐Rumann (Global Change Biology, 2025)
Extreme fire spread events rapidly burn large areas with disproportionate impacts on people and ecosystems. Such events are associated with warmer and drier fire seasons and are expected to increase in the future. Our understanding of the landscape outcomes of extreme events is limited, particularly regarding whether they burn more severely or produce spatial patterns less conducive to ecosystem recovery. To assess relationships between fire spread rates and landscape burn severity patterns, we used satellite fire detections to create day‐of‐burning maps for 623 fires comprising 4267 single‐day events within forested ecoregions of the southwestern United States. We related satellite‐measured burn severity and a suite of high‐severity patch metrics to daily area burned. Extreme fire spread events (defined here as burning > 4900 ha/day) exhibited higher mean burn severity, a greater proportion of area burned severely, and increased like adjacencies between high‐severity pixels. Furthermore, increasing daily area burned also resulted in greater distances within high‐severity patches to live tree seed sources. High‐severity patch size and total high‐severity core area were substantially higher for fires containing one or more extreme spread events than for fires without an extreme event. Larger and more homogenous high‐severity patches produced during extreme events can limit tree regeneration and set the stage for protracted forest conversion. These landscape outcomes are expected to be magnified under future climate scenarios, accelerating fire‐driven forest loss and long‐term ecological change.

Green is the New Black: Outcomes of post-fire tree planting across the US Interior West - Kyle C. Rodman; Paula J. Fornwalt; Zachary A. Holden; Joseph E. Crouse; Kimberley T. Davis; Laura A.E. Marshall; Michael T. Stoddard; Robert A. Andrus; Marin E. Chambers; Teresa B. Chapman; Sarah J. Hart; Catherine A. Schloegel; et al. (Forest Ecology and Management, 2024)

What influences planted tree seedling survival in burned Colorado montane forests? - Laura A.E. Marshall; Paula J. Fornwalt; Camille S. Stevens-Rumann; Kyle C. Rodman; Teresa B. Chapman; Catherine A. Schloegel; Jens T. Stevens (Forest Ecology and Management, 2024)

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

A bird’s eye view of ecosystem conversion: Examining the resilience of piñon-juniper woodlands and their avian communities in the face of fire regime change - Jamie Woolet; Camille S. Stevens-Rumann; Jonathan D. Coop; Liba Pejchar (Forest Ecology and Management, 2023)

Extreme fire spread events and area burned under recent and future climate in the western USA - Jonathan D. Coop; Sean A. Parks; Camille S. Stevens‐Rumann; Scott M. Ritter; Chad M. Hoffman (Global Ecology and Biogeography, 2022)
Aim Wildfire activity in recent years is notable not only for an expansion of total area burned but also for large, single‐day fire spread events that pose challenges to ecological systems and human communities. Our objectives were to gain new insight into the relationships between extreme single‐day fire spread events, annual area burned, and fire season climate and to predict changes under future warming. Location Fire‐prone regions of the western USA. Time period 2002–2020; a future +2°C scenario. Methods We used a satellite‐derived dataset of daily fire spread events and gridded climate data to assess relationships between extreme single‐day fire spread events, annual area burned, and fire season maximum temperature, climate moisture deficit, and vapour pressure deficit. We then developed models to predict fire activity under a 2°C warming scenario. Results Extreme single‐day fire spread events >1,100 ha (the top 16%, >1 SD ) accounted for 70% of the cumulative area burned over the period of analysis. The variation in annual area burned was closely tied to the number and mean size of spread events and distributional skewness towards more large events. For example, we identified 441 extreme events in 2020 that together burned 2.2 million ha across our study area, in contrast to an average of 168 per year that burned 0.5 million ha annually between 2002 and 2019. Fire season climate variables were correlated with the annual number of extreme events and area burned. Our models predicted that the annual number of extreme fire spread events more than double under a 2°C warming scenario, with an attendant doubling in the area burned. Conclusions Exceptional fire seasons like 2020 will become more likely, and wildfire activity under future extremes is predicted to exceed anything yet witnessed. Safeguarding human communities and supporting resilient ecosystems will require new lines of scientific inquiry, new land management approaches and accelerated climate mitigation efforts.

Evidence for declining forest resilience to wildfires under climate change - Camille S. Stevens‐Rumann; Kerry B. Kemp; Philip E. Higuera; Brian J. Harvey; Monica T. Rother; Daniel C. Donato; Penelope Morgan; Thomas T. Veblen (Ecology Letters, 2018)
Forest resilience to climate change is a global concern given the potential effects of increased disturbance activity, warming temperatures and increased moisture stress on plants. We used a multi‐regional dataset of 1485 sites across 52 wildfires from the US Rocky Mountains to ask if and how changing climate over the last several decades impacted post‐fire tree regeneration, a key indicator of forest resilience. Results highlight significant decreases in tree regeneration in the 21st century. Annual moisture deficits were significantly greater from 2000 to 2015 as compared to 1985–1999, suggesting increasingly unfavourable post‐fire growing conditions, corresponding to significantly lower seedling densities and increased regeneration failure. Dry forests that already occur at the edge of their climatic tolerance are most prone to conversion to non‐forests after wildfires. Major climate‐induced reduction in forest density and extent has important consequences for a myriad of ecosystem services now and in the future.